Palatal solitary neurofibroma simulates a salivary gland neoplam. Issue 1 (January 2020) - Sharma, Pooja; Kamboj, Mala; Narwal, Anjali
Abstract: Spindle cell lesions of head and neck are very diverse entities. These may vary from benignity to malignancy. They exhibit a wide diversity ranging from benign fibroma to malignant peripheral nerve sheath tumor. These can be neural, myofibroblastic, fibroblastic, muscle, vascular, odontogenic, epithelial in origin. Such variable tissues involved provide a diagnostic challenge to the oral pathologists. Among these, neural tumors are very rare in oral cavity. A case of spindle cell tumor, which clinically mimicked pleomorphic adenoma, is presented. On histopathology it appeared like a spindle cell tumor. On further investigations like immunohistochemistry, it was diagnosed as neurofibroma. Neurofibromas may present as solitary or associated with neurofibromatosis. In our case, it is of solitary type. Till today only few cases of solitary neurofibromas of hard palate have been reported. Present case report is a rare presentation of solitary extraosseous neurofibroma on hard palate.